2009
DOI: 10.1007/s10103-009-0730-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the furcation area permeability of deciduous molars treated by neodymium:yttrium–aluminum–garnet laser or adhesive

Abstract: The purpose of this in vitro study was to compare the effects of a self-etch adhesive system and neodymium:yttrium-aluminum-garnet (Nd:YAG) laser application on the dentinal permeability of the furcation area of primary molars. After endodontic access, 39 extracted human deciduous molars were divided into three groups: control group (CG), no treatment; adhesive group (AG), self-etching adhesive was applied to the furcation area; laser group (LG), specimens were irradiated with Nd:YAG laser. To evaluate dentin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Lopes‐Silva and Lage‐Marques in an in vitro study concluded that when the floor of the pulp chamber of primary molars was conditioned with Er:YAG laser and covered with 2‐octyl cyanoacrylate, the permeability of dentin was significantly less than when Er:YAG laser was used alone. Another study observed a decrease in dentinal permeability, using Nd‐YAG laser, due to the formation of melted and recrystallized hydroxyapatite crystals, thereby probably occluding the dentinal tubules. Hence, during endodontic treatment, a material which hermetically seals the pulpal floor would be more advantageous than a material which flows only into the accessory canals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopes‐Silva and Lage‐Marques in an in vitro study concluded that when the floor of the pulp chamber of primary molars was conditioned with Er:YAG laser and covered with 2‐octyl cyanoacrylate, the permeability of dentin was significantly less than when Er:YAG laser was used alone. Another study observed a decrease in dentinal permeability, using Nd‐YAG laser, due to the formation of melted and recrystallized hydroxyapatite crystals, thereby probably occluding the dentinal tubules. Hence, during endodontic treatment, a material which hermetically seals the pulpal floor would be more advantageous than a material which flows only into the accessory canals.…”
Section: Discussionmentioning
confidence: 99%
“…Also, microorganisms in biofilms may organize on the external root surfaces of necrotic primary teeth, initiating inter-radicular pathosis 29 . Apart from pathological root resorption, physiological root resorption also opens up the dentinal tubules in the external furcation, thereby hastening the transmission of infection in the area 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques have been used to determine the presence of accessory canals in the pulp chamber floor of molars, especially perfusion with ink [21], infusion of latex [19], lasers [15], digital radiographs, serial histological sections [7,10], scanning electron microscopy (SEM) [1,2,22], cone beam computed tomography [23] and micro-computed tomography (micro-CT) [24]. Analysis with micro-CT in addition to SEM enables optimal evaluation of the floor of the pulp of deciduous molars [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…An associated clinical complication of pulpal infection in the floor region of the pulp of deciduous molars is damage to the ameloblasts of premolars in development, increasing the chances of developing defects in the tooth enamel [5,11,14,15]. Such defects are frequent causes of aesthetic complaints, dentin sensitivity and retention factors of dental biofilm [16].…”
Section: Introductionmentioning
confidence: 99%
“…In their in vitro study, Lopes-Silva and Lage-Marques [21] investigated the effect of Er:YAG laser and 2-octyl cyanoacrylate on the permeability and none of the materials completely prevented the permeability. In a similar in vitro study, Guglielmi et al [4] compared Nd:YAG laser and a self-etch adhesive system (Adhese). They reported that Nd:YAG laser decreased but could not completely eliminate permeability on the pulpal floor.…”
Section: Discussionmentioning
confidence: 99%